2004
DOI: 10.3171/ped.2004.100.2.0183
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of scheduled nonnarcotic analgesic medications in children after suboccipital craniectomy

Abstract: A regimen of minor analgesic therapy, given in alternating doses every 2 hours immediately after craniotomy and throughout hospitalization, significantly reduced postoperative pain scores and LOS in children in whom suboccipital craniotomy was performed. Narcotic and antiemetic requirements were also decreased in association with this regimen. Application of this postoperative analgesia protocol may benefit children and adults in whom various similar neurosurgical procedures are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…However, we were able to find only one report of 'scheduled' nonnarcotic analgesia for patients after craniotomy [9]. This study was performed on children in whom no analgesic was administered prior to surgery.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, we were able to find only one report of 'scheduled' nonnarcotic analgesia for patients after craniotomy [9]. This study was performed on children in whom no analgesic was administered prior to surgery.…”
Section: Introductionmentioning
confidence: 90%
“…Although pain after craniotomy may be less severe than pain after other operations, there is increasing evidence that it remains undertreated in the acute phase [1,2,4]. The use of NSAIDs for analgesia in postcraniotomy patients remains debatable [8], but it has been shown that NSAIDs provide sufficient analgesia and can result in reduced opioid consumption [9].…”
Section: Introductionmentioning
confidence: 99%
“…Regular paracetamol and ibuprofen resulted in lower pain scores, less opioid consumption, decreased antiemetic requirement and shorter hospital lengths of stay than for patients on asneeded treatment. The sample size was very small, however, and confounding by the use of an historical control group was a major risk [21 ].…”
Section: Cranial Neurosurgerymentioning
confidence: 98%
“…One of the only recent studies in this area investigated multimodal analgesia including NSAIDs for pain following paediatric suboccipital craniotomy [21 ]. The first 25 patients were treated with paracetamol and ibuprofen on an as-needed basis.…”
Section: Cranial Neurosurgerymentioning
confidence: 99%
“…Generally, a subpial coagulation of the cerebellar tonsils is preferred in order to decrease the risk of postoperative inflammatory reactions. However, as postoperative pain can be easily controlled medically [223], this kind of advantage might not justify the additional risk of operating in a relatively narrow surgical field without a good visualization. However, as postoperative pain can be easily controlled medically [223], this kind of advantage might not justify the additional risk of operating in a relatively narrow surgical field without a good visualization.…”
Section: Idiopathic Cimmentioning
confidence: 99%